Factors effecting one-year outcome after mechanical ventilation - Günay, Sibel; Sariaydin, Muzaffer; Günay, Ersin (Journal of Thoracic Disease, 2016)
There is a marked increase in the number of patients requiring intensive care unit (ICU) stay, particularly receiving mechanical ventilation in last decades. Mortality and morbidity rates for ICU are high and depend on patients’ underlying disease status, age (especially older age) and duration of mechanical ventilation (1-5). After discharge from ICU, the mortality rate and the disability risk of these patients continue to be high (1,6).